Labouring under a delusion? Scotland's national questions and the crisis of the Scottish Labour Party. Issue 5 (20th October 2021) - Bennett, Stuart; Moon, David S.; Pearce, Nick; Whiting, Sophie
ABSTRACT: In recent years, the Scottish Labour Party has lost its once dominant position in Scottish politics. Its support has collapsed, and it now faces multiple political challenges, relating both to cleavages in Scottish politics over the constitution and Brexit, and to divisions within the party over its leadership and direction. Employing semi-structured elite interviews with key figures within the party hierarchy and focus groups with grassroots activists, this paper examines the causes of this crisis through an analysis of party members' views. It identifies sources of the decline of Scottish Labour in unresolved disagreements over strategy and identity. Unable to coalesce around a distinctly Scottish strategy for competing in a multidimensional, multilevel political space with both civic nationalist challengers and conservative defenders of the constitutional status quo, in 2017, Scottish Labour reasserted a class-based identity, seeking to compete largely on the left–right economic dimension of politics. Instead of marking out a Scottish political identity, the Scottish Labour Party chose leftward national alignment with the Jeremy Corbyn leadership of the UK Labour Party. The electoral and political failure of this strategy offers important lessons for understanding the prospects of multilevel social-democratic parties.